2021
DOI: 10.1111/ppc.12774
|View full text |Cite
|
Sign up to set email alerts
|

Social media addiction and work engagement among nurses

Abstract: Purpose This study was conducted to investigate the relationship between social media addiction (SMA) and work engagement (WE) among nurses in Turkey. Design and methods This cross‐sectional and correlational study was conducted with 205 nurses. In the study, the SMA and WE scales were used. Findings It was determined that there was a negative significant correlation between the SMA and WE variables and that SMA accounted for 2% of WE. Practice implications The controlled use of social media by nurses and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Additionally, the findings of this study, are consistent with the results of another study [ 18 ] that reported that the higher the health information-seeking behavior of nursing students, the better their health-promoting behaviors. Social media has an essential place in the lives of both patients and nurses, and has positive as well as negative impacts [ 35 , 36 ]. It enhances health-related knowledge, improves health outcomes, and aids in the decision-making process regarding healthcare [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the findings of this study, are consistent with the results of another study [ 18 ] that reported that the higher the health information-seeking behavior of nursing students, the better their health-promoting behaviors. Social media has an essential place in the lives of both patients and nurses, and has positive as well as negative impacts [ 35 , 36 ]. It enhances health-related knowledge, improves health outcomes, and aids in the decision-making process regarding healthcare [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, active work engagement is conducive to obtain positive feedback at work and improve the level of work performance, so as to obtain a good sense of career success experience, that is, it helps to promote individual career success (Q. Chen et al, 2021 ; Hoşgör et al, 2021 ). At present, the survey investigating the male nurse's career success is limited.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Another study reported a mean anxiety score of 1.35±2.60 in breast cancer patients in Türkiye (Kiyak and Türkben Polat, 2022). Moreover, in a study investigating the relationship between coronavirus anxiety and professional performance level in healthcare professionals working in emergency medical services, the mean anxiety score was reported as 1.95±1.10 (Hoşgör et al, 2020). For the studies conducted in Türkiye, the scores were similar except for the original validation study with a higher mean score.…”
Section: Resultsmentioning
confidence: 90%